Speech outcomes in children with 22q11.2 deletion syndrome following surgery for velopharyngeal insufficiency. (September 2016) - Jiramongkolchai, Pawina; Kumar, Manvinder S.; Sowder, Derrick; Chinnadurai, Sivakumar; Wootten, Christopher T.; Goudy, Steven L.
Abstract: Objective: The purpose of this study was to identify prognostic factors associated with improved speech outcomes following surgical correction for velopharyngeal insufficiency (VPI) in pediatric patients with 22q11.2 deletion syndrome (22q11DS). Methods: Eighteen patients were identified via retrospective chart review of patients with 22q11DS between 2005 and 2014. Patient characteristics, medical histories, associated comorbidities, surgical procedures, and pre- and postoperative perceptual hypernasality (subjectively rated 1–5 with 5 being the most severe) were gathered for each patient. Results: 12 patients (67%) experienced improvement in hypernasality following corrective surgery for VPI. Higher severity of hypernasality preoperatively was found to be indicative of a lower chance of improvement with VPI surgery. Of 8 patients with a preoperative hypernasality score of 5, 3 (38%) showed improvement in hypernasality postoperatively, while 9 out of 10 (90%) of patients with a preoperative hypernasality score less than 5 showed postoperative improvement. Females were also found to have worse speech outcomes compared to males. Conclusion: 22q11DS patients presenting with severely hypernasal speech preoperatively are less likely to show improvement in hypernasality following corrective surgery for VPI. Those patients with moderate hypernasality are most likely to benefit from surgery.